A RARE CASE OF STATIN-INDUCED NECROTIZING AUTOIMMUNE MYOPATHY - Shuster, Shirley (AACE Clin Case Rep, 2020)
OBJECTIVE: Necrotizing autoimmune myopathy (NAM) is a rare side-effect of statin therapy. We report the case of a patient who developed statin-induced NAM with a review of the clinical presentation and management of this rare entity. The case illustrates the importance of including NAM in the differential diagnosis of persistent myopathy in a statin-exposed individual. METHODS: A 74-year-old male was referred to endocrinology for hypercholesterolemia management in the context of a statin contraindication. He previously developed myositis and rhabdomyolysis secondary to statin therapy, but continued to have persistent proximal lower limb muscle weakness despite statin discontinuation. Rheumatologic and metabolic work-up were negative and neurologic work-up was negative except for a myopathic pattern in the glutei found on electromyography. RESULTS: Due to the persistence of proximal myopathy despite statin discontinuation and myopathic pattern seen on electromyography, NAM was suspected and antibodies against 3-hydroxy-3-methylglutaryl-coenzyme A reductase were sent and came back positive. The patient was treated with the immunosuppressant azathioprine, which resulted in clinical improvement. The patient was started on a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor evolucumab for hypercholesterolemia, which resulted in significant improvement in his lipid panel. CONCLUSION: The case illustrates the presentation and management of statin-induced NAM. We demonstrate the necessity for prompt diagnosis and timely management, as statin therapy is contraindicated and immunosuppressive therapy is warranted. Statin-induced NAM is rare however, it should be included in the differential diagnosis of persistent myopathy despite statin discontinuation. PCSK9 inhibitors are the only alternative therapy for hypercholesterolemia management in patients with statin-induced NAM.